2014
DOI: 10.1007/s11746-014-2557-4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity of Rapeseed Extracts Obtained by Conventional and Ultrasound‐Assisted Extraction

Abstract: Ultrasound-assisted extraction (UAE) and conventional solid–liquid extraction were applied to extract total antioxidants from two rapeseed varieties. The antioxidant capacities (AC) of winter and spring rapeseed cultivars were determined by four different analytical methods: ferric reducing antioxidant power (FRAP), cupric reducing antioxidant capacity (CUPRAC), 2,2′-diphenyl-1-picrylhydrazyl (DPPH), 2,2′-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS). The average AC of the studied rapeseed cultivars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 24 publications
2
14
0
2
Order By: Relevance
“…Similar to the work done by (Annegowda et al, 2010) shows a significant decrease in %ABTS activity with increased sonication time. The probable reason for decreased activity during prolonged sonication might be the cause of a decreased area of diffusion which aligns with this study (Annegowda et al, 2010; Szydłowska‐Czerniak & Tułodziecka, 2014). With continuous extraction of bioactives from tea leaves, it is possible for the diffusion process to move more towards the inner portion of the black tea leaves.…”
Section: Resultssupporting
confidence: 91%
“…Similar to the work done by (Annegowda et al, 2010) shows a significant decrease in %ABTS activity with increased sonication time. The probable reason for decreased activity during prolonged sonication might be the cause of a decreased area of diffusion which aligns with this study (Annegowda et al, 2010; Szydłowska‐Czerniak & Tułodziecka, 2014). With continuous extraction of bioactives from tea leaves, it is possible for the diffusion process to move more towards the inner portion of the black tea leaves.…”
Section: Resultssupporting
confidence: 91%
“…On the other hand, there was no significant correlation between TPC and their ability to reduce cupric ions. It has been suggested that not all of the phenolic compounds are active cupric ion reductor . Therefore, the type of phenolic compounds present in the extract is more influential to the CUPRAC activity than their total content.…”
Section: Resultssupporting
confidence: 76%
“…It is noteworthy that there are significant ( P < 0.01) correlations between DPPH‐RPA ( r = 0.980) and DPPH‐CUPRAC ( r = 0.977) methods used to determine the antioxidant capacity of the studied LSMB and LSFM samples. Similar correlation coefficients ( r = 0.8199–0.9999) between the three antioxidant assays were found in the rapeseed samples …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations